2020
DOI: 10.3390/cancers12082312
|View full text |Cite
|
Sign up to set email alerts
|

Trabectedin and Lurbinectedin Extend Survival of Mice Bearing C26 Colon Adenocarcinoma, without Affecting Tumor Growth or Cachexia

Abstract: Trabectedin (ET743) and lurbinectedin (PM01183) limit the production of inflammatory cytokines that are elevated during cancer cachexia. Mice carrying C26 colon adenocarcinoma display cachexia (i.e., premature death and body wasting with muscle, fat and cardiac tissue depletion), high levels of inflammatory cytokines and subsequent splenomegaly. We tested whether such drugs protected these mice from cachexia. Ten-week-old mice were inoculated with C26 cells and three days later randomized to receive intravenou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 88 publications
(128 reference statements)
0
5
0
Order By: Relevance
“…In addition, Mehl et al (2005) also demonstrated that exercise training reduced splenomegaly in Apc Min/+ transgenic mice 54 . Crucially, exercise decreases cancer-induced splenomegaly effectively, exhibiting results comparable to those achieved through treatment with lurbinectedin (PM01183) and activin receptor type 2 (ACVR2) ligand inhibitors 27 , 55 .…”
Section: Discussionmentioning
confidence: 89%
“…In addition, Mehl et al (2005) also demonstrated that exercise training reduced splenomegaly in Apc Min/+ transgenic mice 54 . Crucially, exercise decreases cancer-induced splenomegaly effectively, exhibiting results comparable to those achieved through treatment with lurbinectedin (PM01183) and activin receptor type 2 (ACVR2) ligand inhibitors 27 , 55 .…”
Section: Discussionmentioning
confidence: 89%
“…Yet, the effectiveness of lurbinectedin in mitigating myocardial damage in mice has been acknowledged. This finding offers a theoretical rationale for considering the use of lurbinectedin in preventing myocardial damage in hypertensive patients ( Aquila et al, 2020 ). Dexamethasone and ondansetron were the most frequently reported concomitant drugs, in line with lurbinectedin’s FDA label recommendations to prevent vomiting in patients receiving lurbinectedin.…”
Section: Discussionmentioning
confidence: 91%
“…In particular, the spleen index is closely related to adaptive immune responses as the spleen serves as a site for immune cell proliferation and differentiation [ 27 ]. Previous studies have shown that the spleen enlarges under immune activation during the occurrence and development of colitis [ 28 , 29 ]. We observed that DSS induction significantly increased the spleen index in mice, while treatment with S. boulardii , heat-killed S. boulardii , and S. boulardii β-glucan reduced the spleen index, indicating an immunomodulatory effect on UC mice.…”
Section: Discussionmentioning
confidence: 99%